L’esperienza estetica come soglia della percezione. Il museo Schneiberg di Torino1 (Itinera, 2023)
Considering the case of the recent creation of the Schneiberg Foundation in Turin, an antique Chinese artworks installation in an historical building, this paper tries to produce a philosophical interpretation of both the artworks and the installation, underlines and investigate the attempt of this project to overcome the distinction between the spectator and his object, involving the viewer in a non- dualistic experience through which he is able to produce his own performance and in that way to create an immersive experience that, like an alchemical process, transforms both his perception and the object of his perception. This text intends also to highlight how this experience is strictly and symmetrically connected to the nature, the meaning and the aim of the objects, i.e. antique imperial Chinese carpets provided of alchemical and philosophical meaning for a performative transformation of their spectator. The paper tries to create, in the end, a performative meaningful experience of a visit to that space and collection.
Keywords: Diderot, Space, Movement, Aesthetics, Philosophy.